Indirubin suppresses ovarian cancer cell viabilities through the STAT3 signaling pathway - Chen L; Wang J; Wu J; Zheng Q; Hu J (Dove Medical Press, 2018)
Lihong Chen, Jinhua Wang, Jianbo Wu, Qiaomei Zheng, Jifen Hu Department of Obstetrics and Gynecology, The First Affiliated Hospital of Fujian Medical University, Fuzhou, China Background: Indirubin is the active component of Danggui Longhui Wan, a traditional Chinese medicine formulation. Due to its anti-inflammation and anti-tumor effects, indirubin has been widely used for the treatment of inflammation, cancer, and other chronic disease. Herein, we aimed to investigate the role and mechanism of indirubin in human ovarian cancer cell proliferation.Materials and methods: The cell viability was determined by Cell Counting Kit-8 and colony formation assays by treatment with different dosages of indirubin over 72 hours. Apoptosis was examined by flow cytometry with fluorescein isothiocyanate Annexin V Apoptosis Detection Kit. Western blot assay was finally applied to analyze the expression of cancer-related STAT3 pathway and its downstream proteins.Results: Indirubin was found to significantly inhibit cell viability and induce apoptosis in 2 human ovarian cancer cell lines. Mechanistic studies revealed that indirubin treatment led to reduced levels of phosphorylated-STAT3, thus repressing the downstream pro-survival proteins and elevating pro-apoptosis ones.Conclusion: Our study provided the evidence for anti-survival activity of indirubin by inhibiting cell viability and inducing apoptosis in human ovarian cancer cells, which involved impaired STAT3 signaling pathway. Our findings further support indirubin as a potential drug candidate against human ovarian cancer. Keywords: indirubin, ovarian cancer, cell viability, STAT3 signaling